Decreased Infections in Recipients of Unrelated Donor Hematopoietic Cell Transplantation from Donors with an Activating KIR Genotype - Tomblyn, Marcie (2010)
Infectious complications following allogeneic hematopoietic cell transplantation (HCT) from unrelated donors (URD) result in significant morbidity. We hypothesized that recipients of an URD with an activating natural killer cell immunoglobulin-like receptor (KIR) (B/x) genotype would have decreased infectious complications due to enhanced NK cell function. We compared the infectious complications in 116 recipients of a graft from a donor with an A/A KIR (n = 44) genotype and a B/x KIR (n = 72) genotype. All recipients participated in the prospective NMDP infection project collecting infection data from conditioning until six months post-transplant. The cohort with a B/x donor had fewer initial bacterial infections by day 180 (A/A: 86% [95% CI, 75 – 95]; B/x: 68% [95% CI, 57 – 78]; p=0.02). There was no difference in the incidence of viral or fungal infections. When accounting for multiple infections, fewer bacterial infections were seen in the B/x cohort (A/A: 3.55/patient; B/x: 2.63/patient; p = 0.09). During the study period, only 19 patients had no infections; of these, 15 had received cells from a B/x KIR donor. The role of donor KIR genotype on infection complications is intriguing and warrants further investigation.